12 + 6x + 6x + 6y = 12 + 12x + 6y
Answer:
y = 11 1/2
Step-by-step explanation:
7y - 63 = y + 3
-y. -7
6y - 63 = 3
+ 63. + 63
6y = 69
/6. /6
y = 11 1/2
Answer:
62.8 inches
Step-by-step explanation:
c = πd
c = 3.14 * 20
c = 62.8 inches
Answer:
3/4
Step-by-step explanation:
Due it having a ratio of .75 instead of the .6875 of the other answers.
The first thing I would probably do is distribute (multiply) the -5/2 into the parenthesis:
= (-5/2)x + (-20/2)
Notice how I am not putting the x into the fraction. This is to make it easier to see the slope-intercept form.
Lets simplify the (-20/2) and then add 7 to both sides:
y - 7 = (-5/2)x - 10
y = (-5/2)x - 3
Your answer would then be:
y = (-5/2)x - 3
y = mx + b
Since it is now in the requested format.